PENGARUH TERPAAN BUDAYA K=POP TERHADAP PERILAKU BERMEDIA SOSIAL GENERASI Z (Studi Pada Penggemar Stray Kids Pengikut Akun Twitter @thestorykids) - Rizky Putri Ramadhani (2023)
The K-Pop culture presence in the technological advance causing some certain behaviors to its audience especially in generation z's social media activity related. This research aim to know the influence of K-Pop Culture exposure to generation z behavior in social media specifically in Stray Kids' fan circles who follow @thestorykids twitter account. Theory that will be used as the reference in this research is individual difference theory. The method that will be used in this research is quantitative method with explanation research which will be done by closed questionnaire. The result showed that there's a strong correlation between the K-Pop culture exposure and generation z behavior in social media with 0,760 of correlation coefficient. The exposure of K-Pop culture has a significant positive effect on generation z behavior in social media with 57,8% of coefficient of determination. Then, the results showed that in variable X, the frequency became the most significant dimension with the highest average value in variable X. Meanwhile, in variable Y, the most significant dimension with the highest average value is the cognitive dimension. The results of the study are also in line with the theory of individual differences where individuals as the target audience exposed by the content of media messages, which in this study are fans of Stray Kids, get certain effects that varies individually. So, it's known that there's an influence between K-Pop culture exposure to generation Z's social media behavior. Researcher hope that future research can examine related relevant topics more deeply.